Injury Severity Based Black Spot Identification: Assessment of the Method in the Municipality of Hjørring - Sørensen, Michael; Pedersen, Søren Kromann (Proceedings from the Annual Transport Conference at Aalborg University, 2007)
A new Danish road safety plan for 2001-2012 was published in 2000. The focus for the plan was to reduce the number of fatalities and seriously injured and not slightly injured. As a reaction to the new objective, a method for injury severity based black spot identification was developed at Aalborg University. In this paper the method has been tested in the Municipality of Hjørring and compared with normal black spot identification. The objectives have been to evaluate to what extent the new method increases the focus on the most severe accidents and to examine if the new method contribute to road safety work that are more cost effective. An injury severity based and a normal black spot identification have been preformed and the number and severity of accidents on the identified locations have been compared. The comparison indicates that the injury severity based method with advantage could be used for primarily road sections, because it increases the focus on locations with severe accidents. The evaluation also consists of an analysis of whether the identified locations are true or false black spots. The study includes too few locations to make it possible to make a final conclusion about this question. However, for the specific case it has been shown that the new method is as effective as the normal method for identifying true black spots. Finally a comparison of first year rate for treatment for black spots from the two identifications has been made. Again, there is to little data to make a general conclusion, but among the examined locations the first year rate for the proposed treatment was highest for the locations that were identified by the injury severity based method.